A complex exile: homelessness and social exclusion in Canada - Dej, Erin (UBC Press, 2020)
"A Complex Exile shows that the homelessness sector inadvertently reinforces the social exclusion of people who are homeless. Over 235,000 people couch surf, stay in emergency shelters, and live on the street in Canada every year. However, the very policies, practices, and funding models that exist to house the homeless, promote social inclusion, and provide mental health care form a homelessness industrial complex. These practices emphasize personal responsibility and individualized responses that ultimately serve to subtly exclude people. This book goes beyond bio-medical and psychological perspectives on homelessness, mental illness, and addiction, to call for a transformation in how we respond to homelessness in Canada."--